ijee 2022
DOI: 10.48165/ijee.2022.58314
|View full text |Cite
|
Sign up to set email alerts
|

Pulses Yield Gap Minimization: Consequences of CFLD-Pulses in India

Abstract: The present study is the analysis of large scale data (31949 ha area and 79873 farmers) generated through the CFLD on pulses across the major pulses growing states under the ICAR-ATARIs of Kanpur, Jodhpur, Pune, Jabalpur, Kolkata, Guwahati, Hyderabad, Bangalore and Patna. The present analysis represented the pulse crops of kharif (pigeon pea-5556 ha, black gram-6067 ha and green gram-2689 ha), rabi (chickpea-8376 ha, lentil 3747 ha and field pea-1890 ha) and summer (green gram-3624 ha) seasons. The average per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…These findings are in line with findings of Singh et al, (2020c). Similarly, the yield gap minimization in pulses was reported by Nain et al, (2014); Nain et al, (2015); Dubey et al, (2018) & Dubey et al, (2022.…”
Section: Extension Gapsupporting
confidence: 91%
“…These findings are in line with findings of Singh et al, (2020c). Similarly, the yield gap minimization in pulses was reported by Nain et al, (2014); Nain et al, (2015); Dubey et al, (2018) & Dubey et al, (2022.…”
Section: Extension Gapsupporting
confidence: 91%
“…This may due to unawareness about high yielding varieties, increased extension yield gap as a result of farmers' ignorance to adopt better farming practices; this suggests that farmers need to be strongly encouraged to embrace improved farming practices in pulse crop rather than sticking with traditional local methods. These findings in line with findings reported by Kumar et al (2022) [5] , Singh et al (2020) [11] , Dubey et al (2022) [2] and Sunitha et al (2020c) [15] reported that the highest extension gap was observed in pigeon pea. This extension yield gap may minimized by promoting some extension activities, organizing awareness training programme to the farmers about high yielding varieties and organizing Krishimela's.…”
Section: Extension Gapsupporting
confidence: 90%
“…The extension gap ranged between 0.88 q/ha and 3.02 q/ha in the districts under study (Figure 1) in three www.extensionjournal.com states emphasizes the need to educate the farmers regarding improved technologies like improved high yielding varieties and new agricultural practices by the extension personnel to reverse this trend of wide extension gap. Similar findings were reported by Dubey et al (2018) [4] , Dubey et al (2022) [5] in pulses, Kumar et al (2022) [8] in rapeseed and mustard and Kumar et al (2023) [9] in pigeon pea. Singh and Gautam (2016) [21] opined that the extension gap in yield of sesame can be minimized by disseminating the technology package and upscaling the adoption percentage to increase production and productivity.…”
Section: Extension Gapsupporting
confidence: 85%